Determination of Total Phenolic Content Using the Folin-C Assay: Single-Laboratory Validation, First Action 2017.13. (23rd November 2019) - Kupina, Steve; Fields, Chris; Roman, Mark C; Brunelle, Sharon L
Abstract: A single-laboratory validation of a method using Folin & Ciocalteu's phenol reagent (Folin-C reagent) for determination of total phenolic content of selected dietary supplement extracts was performed. The method is composed of a water extraction of dried extracts with sonication followed by reaction with the Folin-C reagent. The resulting colorimetric reaction is measured at 765 nm and compared with a standard curve generated with gallic acid standard solutions. The validation results were compared with Standard Method Performance Requirement (SMPR ® ) 2015.009, developed by the Stakeholder Panel on Dietary Supplements. The method demonstrated acceptable within-day RSDr of 1.96–7.47% for the five matrixes studied (grape seed extract, grape skin extract, black tea extract, green coffee extract, and cocoa extract). When gallic acid was spiked into maltodextrin (a surrogate dietary supplement carrier) at 30 or 70%, the recovery ranged from 91 to 104%, within the acceptable range established by SMPR 2015.009. Selectivity testing with glucose, fructose, and sucrose demonstrated no positive interference by these compounds. Finally, ruggedness studies demonstrated no significant effects due to changes in the heating apparatus, test material weight, read time after reaction, amount of Folin-C reagent, reaction time, reaction temperature, and amount of Na2 CO3 . The single-laboratory validation results support adoption of the method as First Action Official Method SM 2017.13 and further evaluation in a collaborative study.